2011
DOI: 10.1098/rspb.2011.1289
|View full text |Cite
|
Sign up to set email alerts
|

A ‘living fossil’ eel (Anguilliformes: Protanguillidae, fam. nov.) from an undersea cave in Palau

Abstract: We report the discovery of an enigmatic, small eel-like fish from a 35 m-deep fringing-reef cave in the western Pacific Ocean Republic of Palau that exhibits an unusual suite of morphological characters. Many of these uniquely characterize the Recent members of the 19 families comprising the elopomorph order Anguilliformes, the true eels. Others are found among anguilliforms only in the Cretaceous fossils, and still others are primitive with respect to both Recent and fossil eels. Thus, morphological evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
123
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(141 citation statements)
references
References 24 publications
16
123
1
1
Order By: Relevance
“…The specimens referred in the present work are recognized as true Anguilliformes, commonly known as eels, because their long and cylindrical snake-like bodies, their absence of a pelvic fin, and their pectoral fin located in the middle of the trunk far from the ventral border and behind the fourth vertebra ( Figure 3.1) are distinctive characters of this order (Nelson, 2006;Wiley and Johnson, 2009;Johnson et al, 2011;Chen et al, 2014). Additionally, the Belisario Domínguez eels cannot belong in the Saccopharyngiformes since the latter is a group of highly specialized fishes lacking their opercular bones and branchiostegal rays, whereas in the Mexican specimens such bones are present (Figure 3.3).…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 2 more Smart Citations
“…The specimens referred in the present work are recognized as true Anguilliformes, commonly known as eels, because their long and cylindrical snake-like bodies, their absence of a pelvic fin, and their pectoral fin located in the middle of the trunk far from the ventral border and behind the fourth vertebra ( Figure 3.1) are distinctive characters of this order (Nelson, 2006;Wiley and Johnson, 2009;Johnson et al, 2011;Chen et al, 2014). Additionally, the Belisario Domínguez eels cannot belong in the Saccopharyngiformes since the latter is a group of highly specialized fishes lacking their opercular bones and branchiostegal rays, whereas in the Mexican specimens such bones are present (Figure 3.3).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Therefore, it is not presently feasible to classify Cretaceous eels within families solely created to include their Cenozoic and extant relatives. At the beginning of the present decade, Johnson et al (2011) described Protoanguilla palau, a species which was placed in its own family, Protoanguillidae, as a putative living sister group of both Cenozoic and extant eels. However, succeeding studies (Santini et al, 2013;Chen et al, 2014) identified this species at the base of the living eels as the sister group of the family Synaphobranchidae.…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 1 more Smart Citation
“…The 5 Mastigias subspecies inhabiting different marine lakes, described by Dawson (2005), must fit in this case. Recently, a living fossil eel belonging to a new family in the order Anguilliformes was described from an undersea cave in Palau (Johnson et al, 2011). The divergence time between the new species and other eels was surprisingly estimated at 200 million years ago from phylogenetic analysis based on mitochondrial genome sequences, indicating the possibility that this species has been isolated in the undersea cave and speciated.…”
Section: Perspective On Evolution In the Marine Lakesmentioning
confidence: 98%
“…The subfamily was later elevated to family status by Parenti (1984) and also recognized as a valid family by Nelson (1994). Protoanguilla palau Johnson et al 2012, an unusual eel collected from a cave at the Palau Islands, was also described as a new genus and new family (Protanguillidae) by the original species' authors.…”
Section: New Taxa: 1980-presentmentioning
confidence: 99%